Law enforcement in Malaysian securities markets - Yeon, Asmah Laili; Mohd Shamsudin, Faridahwati (International Organization of Scientific Research (IOSR), 2012)
The objective of this paper is to discuss issues of law enforcement in Malaysian Securities Markets.This survey was conducted among 107 principal and representative licensees registered with the Securities Commission of Malaysia.They consist of licensed dealers, investment advisers and fund managers.The majority of the respondents were capital markets and services representative licensees (CMSRL), while only 17 respondents were capital markets and services licensees.On a scale of one to five, respondents were found to be generally satisfied with the roles and responsibilities of enforcement bodies i.e. Securities Commission and Bursa Malaysia (mean of satisfaction = 3.660 to 3.952).The study shows that there is a positive relationship between the views and attitudes of respondents towards the implementation of the legal philosophy by the enforcement bodies (r= .524, r= .480). As the main enforcement agencies, Securities Commission and Bursa Malaysia should further enhance efforts to monitor and enforce the law of capital markets. In conclusion, this paper provides useful information in relation to factors contributing to non compliance of participants of the capital markets. The enforcement bodies can implement measures on how to curb the unethical behaviour by carrying out ethics training and introducing new rules and regulations for the industry.